In Search of Informed Discretion: An Experimental Investigation of Fairness and Trust Reciprocity - Maas, Victor S.; van Rinsum, Marcel; Towry, Kristy L. (The Accounting Review, 2012)
ABSTRACT This paper investigates managerial discretion in compensation decisions in a team setting, in which a measure of the team's aggregate performance is readily available from the accounting system. Specifically, we examine the willingness of managers to obtain additional, costly information that would supplement this measure and allow the managers to more accurately assess individual contributions to team output. Using theory from behavioral economics that incorporates social preferences (i.e., fairness and trust reciprocity) into the managers' utility function, we predict and demonstrate experimentally that managers' willingness to obtain the costly information increases as the team's aggregate performance becomes a more noisy measure of individual performance. Further, we predict and demonstrate that managers' willingness will be greater for relatively high versus relatively low levels of aggregate performance. The study contributes to the literature on subjective performance evaluation by identifying how social preferences influence managers' use of discretion in evaluation processes. Data Availability: The data from this study and the set of instructions for the experimental task are available from the researchers upon request.